Russian Federation : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2004)
This report on the Russian Federation's Observance of Standards and Codes highlights the Data Module and response by the authorities. Russia's statistical system has made good progress in adopting international statistical methodologies in response to the need to capture in the statistics the country's transition to a market economy. These improvements have been achieved notwithstanding the statistical challenges posed by extraordinary economic events during the transition, including the financial crisis of 1998. Appropriate measures are taken in the assessment and validation of source data, intermediate data, and statistical outputs.